'In Sweden, girls are allowed to kiss girls, and boys are allowed to kiss boys': Pride Järva and the inclusion of the 'LGBT other' in Swedish nationalist discourses. (June 2018) - Kehl, Katharina
This article discusses Pride Järva, a 'gay pride' march organised by right-wing publicist Jan Sjunnesson in Stockholm's northern suburbs. Analysing the event, and in particular a speech made by Sjunnesson during the parade in July 2016, I argue that it is indicative of the specific ways in which right-wing actors in Europe increasingly enlist LGBT rights in nationalist, xenophobic and racist projects of exclusion. As markers of tolerant and progressive 'Europeanness', they are used to construct and reproduce dangerous racialised and Islamic others along lines of sexuality and gender, a narrative that resonates with established notions of Swedish gender exceptionalism as well as homonationalist-orientalist narratives of threat and protection. Despite their history of actively opposing the expansion of LGBT rights, Sjunnesson and his political associates combine these narratives with a conceptualisation of LGBT issues as private and depoliticised to produce themselves as the 'true' protectors of LGBT rights in Sweden.